PENGARUH GAYA KEPEMIMPINAN KEPALA SEKOLAH, MOTIVASI DAN LINGKUNGAN KERJA TERHADAP KINERJA GURU SMK PUSAKA 1 JAKARTA - Sanim; Edi (Pasca Sarjana Universitas Satya Negara Indonesia, 2016)
This research aimed to analyze the influence of the principal's leadership style, motivation and work environment on teacher performance, and determine which variables are most strongly affect the performance of teachers. The study population was 48 teachers of SMK Heritage I Jakarta and the entire population of the research sample. The result is the percentage of variables influence the leadership style of the principal (X1) to variable teacher performance that is equal to 36.9% and the correlation coefficient of 0.541 ry1, the influence of work motivation (X2) to variable performance of teachers is 31.6% and the correlation coefficient ry2 amounted to 0.615, the influence of the working environment (X3) on teacher performance variable that is equal to 38.8% and the correlation coefficient of 0.567 ry3, when compared to the three turned out to be the working environment have a greater influence. Simultaneously the dependent variable of teacher performance is determined by the independent variables jointly by 58.2%. That is 100% - 58.2% = 41.8% of teacher performance is influenced by other factors outside of the independent variables in this research.